2022
DOI: 10.1172/jci156876
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-F–expressing neutrophils are essential for creating a profibrotic microenvironment in renal fibrosis

Abstract: The roles of neutrophils in renal inflammation are currently unclear. On examining these cells in the unilateral ureteral obstruction murine model of chronic kidney disease, we found that the injured kidney bore a large and rapidly expanding population of neutrophils that expressed the eosinophil marker Siglec-F. We first verified that these cells were neutrophils. Siglec-F + neutrophils were recently detected in several studies in other disease contexts. We then showed that a) these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Moreover Siglec8+ (human homolog to murine SiglecF) were increased in patients with Asthma-COPD overlap. Other studies have reported that SiglecF+ neutrophils have a prolonged lifespan, hypersegmented nuclei, increased mobility and an enhanced inflammatory phenotype ( 67 71 ). The current study also found that SiglecF+ neutrophils were present in the airways along with NET accumulation after AA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover Siglec8+ (human homolog to murine SiglecF) were increased in patients with Asthma-COPD overlap. Other studies have reported that SiglecF+ neutrophils have a prolonged lifespan, hypersegmented nuclei, increased mobility and an enhanced inflammatory phenotype ( 67 71 ). The current study also found that SiglecF+ neutrophils were present in the airways along with NET accumulation after AA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LTB4/BLT1 has been reported to contribute to neutrophil, eosinophil, helper T‐cell and dendritic cell chemotaxis 14,29,30 . Although CD170, also known as Siglec‐F, is a widely used eosinophil marker in mice, 31,32 some subsets of neutrophils also express Siglec‐F 33,34 . Therefore, it is possible that some CD170+ cells are neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, single‐cell transcriptomic analysis was used to distinguish specific sub‐populations of neutrophils without providing their precise phenotypic characterization. Finally, a murine model of renal fibrosis showed that a new Siglec‐F‐expressing neutrophil subtype promoted collagen I production by fibroblasts 352 . Siglec‐F‐positive neutrophils were also able to produce collagen I directly.…”
Section: Large‐vessel Vasculitis (Lvv)mentioning
confidence: 99%